Local wisdom based learning and sustainable business development model - Suranto, Suranto; Syah, Muhammad Fahmi Johan; Nurgiyatna, Nurgiyatna (Edelweiss Applied Science and Technology, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a significant concern for the government, particularly within the creative industry sector. The government emphasizes sustainable management throughout the entire value chain through the "Astacita" program. Consequently, this study aimed to develop a sustainable business learning model for MSMEs in the batik industry. Although batik production experienced a decline, it has since been revitalized through various innovations and creative efforts to maintain its relevance in the market. Key steps include providing motivation, enthusiasm, and support to prospective future generations to ensure the continuation of ancestral businesses. However, there is a lack of awareness among youth regarding independent business ventures and entrepreneurship. The absence of both soft skills and hard skills, coupled with limited knowledge and abilities across affective, cognitive, and psychomotor domains, presents significant challenges within the batik industry. Therefore, it is essential to develop a sustainable business learning model by identifying the characteristics of prospective entrepreneurs—both internal and external factors—exploring local wisdom through education and development, and strengthening education, training, guidance, counseling, mentoring, and empowerment initiatives. Additional solutions involve promoting life skills, soft skills, hard skills, as well as vocational and occupational competencies to enhance capabilities and achieve sustainable outcomes. This study employed mixed methods, utilizing structural equation modeling to analyze concepts and formulate variables influencing business character, learning models, and sustainability, all rooted in local wisdom. The results indicated that manifest variables effectively interpreted each latent variable, demonstrating strong interrelationships among them.